Delamination Tendency of Repair Mortar Incorporating Crumb Rubber. (2017) - Kristiawan, Stefanus A.; Hapsari, Amanah N.D.
Abstract: The success of repair material to extend the service life of infrastructures will be determined by its performance and durability. The delamination tendency of this material may be a crucial factor that governs its performance and durability. This paper investigates the delamination tendency of repair mortar incorporating crumb rubber at various contents. The beneficial effect of incorporating crumb rubber to reduce the risk of delamination is discussed. A simulation of shear stress due to differential shrinkage in the interface between repair mortar and substrate concrete is accomplished to highlight the important of material properties (elastic modulus, creep and shrinkage) with regards to delamination tendency.